Strategic Training and its impact on The Performance of the inspectors General offices - جثير, سعدون حمود; نصيف, اخلاص خالد (Journal of Economics and Administrative Sciences, 2015)
The research aims  to study strategic training and its impact on improving the performance of the inspectors general offices in Iraqi ministries, through two variables strategic training Which include Four Dimensions ( Strategic analysis , Formulation of Training Strategy , Implement the Training Strategy , Evaluation ) and Performance included Three dimensions ( Efficiency , Effectiveness , Added-Value).This research problem is that the Offices of Inspectors rely on pre-made training Programs  received from training centers without designing the training programs that provide the employees with the skills and abilities that lead to the implementation of the current and future goals of the organization.The most important conclusion it that the the application of the stages of the strategic training process contributes to improving the performance of these offices , and the most important recommendations is the necessity of the support of the top management in the inspectors general offices of the strategic role that could be played by training by the application of strategic training to be a starting point to provide employees in these offices with the skills and capabilities to implement the strategic goals , and the need for integration of environmental changes in the selection of training programs , and the necessity of taking into consideration the future jobs that will be developed when planning for training and the and selection of training programs based on that